2014
DOI: 10.2174/1871527313666140806144425
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Parkinson's Disease

Abstract: Parkinson's disease (PD) is a chronic neurodegenerative disease with major impacts on patients' lives and on society as a whole. It is one of the most common neurodegenerative diseases in the world, second only to Alzheimer's disease. Low levels of production of dopamine (DA) are associated with PD. This is caused by a progressive loss of neurons in the midbrain's substantia nigra, resulting in changes in neural conduction within the nigrostriatum. Research into PD has been going on since 1960, still there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…[1][2] Thus over the years a lot of research has been focused on the development of greener processes. 3 Benzimidazole derivatives exhibit various biological and pharmaceutical properties [4][5][6][7] . Recently it has been found that benzimidazole derivatives are useful as fluorescent chemo sensors for Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Thus over the years a lot of research has been focused on the development of greener processes. 3 Benzimidazole derivatives exhibit various biological and pharmaceutical properties [4][5][6][7] . Recently it has been found that benzimidazole derivatives are useful as fluorescent chemo sensors for Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that several 1,2-disubstituted benzimidazoles [2,3] are potent inhibitors of RNA viruses and this effect encouraged intensive efforts to prepare and evaluate other derivatives. 2-Mercaptobenzimidazole is derivative of benzimidazole exhibited a wide variety of interesting biological activities such as antimicrobial [4], anticonvulsant [5], antidiabetic [5], antiulcer agent [6], Antibacterial [7] and antifungal [7], etc. Aceto group containing benzimidazole which reacts with different amine produced azomethine moiety [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years of active research, benzimidazole is reported to shown wide range of therapeutic activities [1][2][3][4][5][6][7]. Albendazole, mebendazole, thiabendazole as antihelmintics; omeprazole, lansoprazole, pantoprazole as proton pump inhibitors; astemizole as antihistaminic; enviradine as antiviral; candesarten cilexitil and telmisartan as antihypertensive which contains benzimidazole as active pharmacophore.…”
Section: Introductionmentioning
confidence: 99%